Multilateralism and the World Trade Organisation : the architecture and extension of international trade regulation - Wilkinson, Rorden, 1970- (Routledge advances in international political economy., 2000)
This book explores the significance of the establishment of the World Trade Organisation (WTO), as well as some of the issues brought into sharper focus by the Seattle demonstrations of 1999. Located within the broader study of global governance, Multilateralism and the World Trade Organisation offers a critical examination of the legal framework of the WTO. The book uncovers a series of discriminatory practices embedded in the WTO's legal framework, which act to the disadvantage of smaller, developing and transitional states.